Pengaruh Persepsi Etika Bisnis Islam Terhadap Perilaku Pedagang Batak Muslim di Jakarta Studi Kasus Pada Organisasi Pedagang Batak Muslim KKMM (Kerukunan Keluarga Masyarakat Mompang Jae) - HP, Ustman Hady; Septiarini, Dina Fitrisia (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research was aimed to find out the effect of Islamic business ethicâs perceptionÂ against the behavior of Batak Moslemâs merchants in Jakarta. This research usedÂ questionmaires in primary data collection and quantitative approaches. Experiments wereÂ done using simple linear regression, where the dependent variable (Y) is behavior of BatakÂ Moslemâs merchant and the independent variable (X) is Islamic business ethics. The researchÂ sample was taken by probability sampling with simple random sampling method. Theresearch sample was 65 Batak Moslemâs merchants who were members of KKMM in Jakarta.Based on the findings, it obtained simple linear regression equation: Y = 22,376 +Â 0,279X. The results of this research showed that the influence of Islamic business ethics hasÂ positive effect and signifficant against the behavior of Batak Moslemâs merchants who wereÂ members of KKMM in Jakarta.The R2 on this research showed the number 0.423, which mean that 42.3% of behaviorÂ of Batak Moslemâ merchants can be explained by the variables of Islamic business ethics.Â These results also explain that there are other variables were greater (57.7%) were able toÂ explain the behavior of Batak Moslemâs merchants.